Peran Perencanaan Dan Pengembangan Sdm Pada Umkm Kripik Balado Salsabila Kubu Parak Karakah - Adiprana Mahendra; Mutiara Dela; Zilfa Aulia Marsandi; Ramdhani Bayu Putra; Hasmaynelis Fitri (CV. ITTC INDONESIA, 2025)
This study aims to analyze the role of human resource planning and development in the small enterprise Kripik Balado Salsabila, located in Kubu Dalam Parak Karakah. In the face of market competition and the need for business sustainability, human resource management becomes a crucial aspect. This research uses a descriptive qualitative method with a case study approach. The results show that human resource planning is carried out informally based on production needs, while human resource development is implemented through on-the-job training. The main supporting factors include a harmonious work environment and operational flexibility, while inhibiting factors consist of limited funding and the absence of a structured HR management system. In conclusion, human resource planning and development play a significant role in improving productivity and sustaining the business operations of this small enterprise.